2015
DOI: 10.1214/15-aoas863
|View full text |Cite
|
Sign up to set email alerts
|

Extremes on river networks

Abstract: Max-stable processes are the natural extension of the classical extreme-value distributions to the functional setting, and they are increasingly widely used to estimate probabilities of complex extreme events. In this paper we broaden them from the usual situation in which dependence varies according to functions of Euclidean distance to situations in which extreme river discharges at two locations on a river network may be dependent because the locations are flow-connected or because of common meteorological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
191
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(192 citation statements)
references
References 50 publications
0
191
1
Order By: Relevance
“…However, our study as well as the one by Asadi et al (2015) for the Danube river has shown that the Euclidean distance between stations has low explanatory power in the case of regional floods. We found that river distance is a suitable dependence measure for describing the change in dependence along the river network.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…However, our study as well as the one by Asadi et al (2015) for the Danube river has shown that the Euclidean distance between stations has low explanatory power in the case of regional floods. We found that river distance is a suitable dependence measure for describing the change in dependence along the river network.…”
Section: Discussioncontrasting
confidence: 60%
“…The Euclidean distance is used as a standard distance measure when looking at spatial extremes such as precipitation, temperature, and wind (Asadi et al, 2015). However, our study as well as the one by Asadi et al (2015) for the Danube river has shown that the Euclidean distance between stations has low explanatory power in the case of regional floods.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Exploring one potential approach, some recent research has explored the development of models based on max-stable processes for river network data [1]. However max-stable processes are only suitable for spatial extreme data sets that exhibit asymptotic dependence [1], a property where the largest values in each variable can occur concurrently.…”
Section: Introductionmentioning
confidence: 99%
“…Exploring one potential approach, some recent research has explored the development of models based on max-stable processes for river network data [1]. However max-stable processes are only suitable for spatial extreme data sets that exhibit asymptotic dependence [1], a property where the largest values in each variable can occur concurrently. Therefore they are practically infeasible for higher-dimension problems such as models of national scale river flow or rain gauge networks, because simultaneous extreme flows are unlikely in any one event over all sites.…”
Section: Introductionmentioning
confidence: 99%